The Destiny of the Open Cluster NGC 6530: Past and Future - Jia, Delong; Yu, Heng; Shao, Zhengyi; Li, Lu (The Astronomical journal, 2024)
Studying the structures of open clusters is crucial for understanding stellar evolution and galactic dynamics. Based on Gaia DR3 data, we apply the hierarchical clustering algorithm to the young open cluster NGC 6530 and group its members into five substructures. By linear tracing with the kinematic information of their members, we find that sub 1 is the core of the cluster. It is expanding slowly. Sub 2 consists of less-bound members, which began escaping from the core about 0.78 Myr ago. Sub 3 is associated with a young star-forming region. It will merge with the core after 0.72 Myr. Sub 4, as an outskirts group, is also moving toward the core but will not end up falling in. Sub 5 is composed of less-bound members with field contamination. This work reveals the complex internal structure and evolutionary trends of the cluster NGC 6530. It also shows the potential of the hierarchical clustering algorithm in star cluster structure analysis.